Docking of CuI and AgI in Metal–Organic Frameworks for Adsorption and Separation of Xenon. (26th January 2021) - Wang, Haoze; Shi, Zhaolin; Yang, Jingjing; Sun, Tu; Rungtaweevoranit, Bunyarat; Lyu, Hao; Zhang, Yue‐Biao; Yaghi, Omar M.
Abstract: We present a metal docking strategy utilizing the precise spatial arrangement of organic struts as metal chelating sites in a MOF. Pairs of uncoordinated N atoms on adjacent pyrazole dicarboxylate linkers distributed along the rod‐shaped Al–O secondary building units in MOF‐303 [Al(OH)(C5 H2 O4 N2 )] were used to chelate Cu I and Ag I with atomic precision and yield the metalated Cu‐ and Ag‐MOF‐303 compounds [(CuCl)0.50 Al(OH)(C5 H2 O4 N2 ) and (AgNO3 )0.49 Al(OH)(C5 H2 O4 N2 )]. The coordination geometries of Cu I and Ag I were examined using 3D electron diffraction and extended X‐ray absorption fine structure spectroscopy techniques. The resulting metalated MOFs showed pore sizes matching the size of Xe, thus allowing for binding of Xe from Xe/Kr mixtures with high capacity and selectivity. In particular, Ag‐MOF‐303 exhibited Xe uptake of 59 cm 3 cm −3 at 298 K and 0.2 bar with a selectivity of 10.4, placing it among the highest performing MOFs. Abstract : Pairs of uncoordinated N atoms on adjacent pyrazole dicarboxylate linkers distributed along the rod‐shaped Al–O secondary building units of a MOF were used to chelate Cu I and Ag I with atomic precision (see picture). The resulting metalated MOFs showed pore sizes matching the size of Xe, thus enabling the binding of Xe from Xe/Kr mixtures with high capacity and selectivity.